Ginsenoside Rf relieves mechanical hypersensitivity, depression‐like behavior, and inflammatory reactions in chronic constriction injury rats. (11th February 2019) - Li, Yangyi; Chen, Chengbo; Li, Shunyuan; Jiang, Changcheng
Abstract : The aim of this study was to investigate whether ginsenoside Rf can effectively relieve pain hypersensitivity in a neuropathic pain rat model. Neuropathic pain was induced in rats by chronic constriction injury (CCI) to the right sciatic nerve. Ginsenoside Rf was administered intraperitoneally after CCI surgery. The von Frey filament test and forced swimming test were performed to examine pain hypersensitivity and depression‐like behavior in rats. Western blot was used to measure the levels of inflammatory cytokines in the dorsal root ganglion (DRG) and the spinal cord. Pretreatment of ginsenoside Rf for 7 days did not affect the onset of mechanical allodynia in CCI rats; however, a single dose of ginsenoside Rf 1 day after surgery attenuated established mechanical allodynia in CCI rats. Additionally, chronic treatment of ginsenoside Rf 1 week before and 2 weeks after CCI surgery diminished mechanical allodynia and depression‐like behavior without affecting spontaneous locomotor activity in CCI rats. Furthermore, in CCI rats, chronic ginsenoside Rf treatment partially reversed the upregulation of proinflammatory cytokines in the spinal cord and/or the DRG but elevated IL‐10, an anti‐inflammatory factor, in the DRG. Ginsenoside Rf alleviated neuropathic pain and its associated depression and restored the balance between proinflammatory and anti‐inflammatory cytokines. Our results suggest that ginsenoside Rf may be a potential therapy for nerve injury‐induced neuropathic pain.